Awareness of cervical cancer and its screening methods in Indian women - Singh, Khushboo; Goel, Alka; Attri, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: In spite of effective screening methods, cervical cancer continues to be a major public health problem in India. Therefore, the present study was carried out to assess the knowledge of cervical cancer and its screening among women, it also focuses on the reasons for not undergoing regular screening and the effect of counseling for the same. Method: 400 women were randomly enrolled from the women attending/visiting/working at a tertiary hospital. They were asked questions related to cervical cancer. All answers were obtained verbally and recorded in the questionnaire by the same investigator. Results: Out of 400 women, only 103 were aware of cervical cancer as well as its screening, and only 10 of them were undergoing regular screening. Among those who were aware of cervical cancer, majority (95.14%) were health care workers and most of them got this knowledge form their textbooks. After counseling, all except 6 women were willing for regular screening. The reason for refusal for the same was either they believed they were not at risk or they found pelvic examination uncomfortable. Conclusions: The study found that women had poor knowledge about cervical cancer and its screening. Awareness was higher among the women who had received higher education or were healthcare workers. However, cervical cancer screening rate was low even in these women. Government and health care professionals need to actively promote awareness of the risk factors of cervical cancer and encourage women to undergo regular Pap smear as a cervical cancer screening method.